ANALISIS PENGARUH PROFITABILITAS, STRUKTUR ASET DAN KEBIJAKAN DEVIDEN TERHADAP STRUKTUR MODAL (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020) - Priantoko, Agung; Widaryanti, Widaryanti (STIE PENA, 2022)
This study aims to analyze the analysis of the effect of profitability, asset structure and dividend policy on capital structure (Case Study on Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2020 Period) The population used in this study are companies that are included in the category of Manufacturing companies listed on the IDX in 2016-2020 are 148 companies. The sample in this thesis research amounted to 23 companies in the 5year period of research, so that the research data amounted to 115 data. The method of data collection is through documentation studies, the analysis method uses multiple regression analysis with the Ordinary Least Square (OLS) simple least squares method. The results of hypothesis testing in this study indicate that Profitability and Asset Structure have a positive effect on Capital Structure, while dividend policy has no effect on Capital Structure.Keywords: Profitability, Asset Structure, Dividend Policy and Capital Structure